Answer to Question #214109 in Differential Equations for Fiina

Question #214109

Solve the ordinary di erential equation

y'' + 2y' + 5y = 4e-x + 17 sin 2x:


1
Expert's answer
2021-07-06T15:54:32-0400

Given the differential equation


"y'' + 2y' + 5y = 4e^{-x} + 17 \\sin 2x"

We can rewrite the equation as


"\\frac{d^{2} y(x)}{d x^{2}}+2 \\frac{d y(x)}{d x}+5 y(x)=4 e^{-x}+17 \\sin (2 x)"

The general solution will be the sum of the complementary solution and particular solution. We thus find the complementary solution by solving


"\\frac{d^{2} y(x)}{d x^{2}}+2 \\frac{d y(x)}{d x}+5 y(x)=0"


Assume a solution will be proportional to "e^{\\lambda x}" for some constant "\\lambda."  

Substitute "y(x)=e^{\\lambda x}" into the differential equation:


"\\frac{d^{2}}{d x^{2}}\\left(e^{\\lambda x}\\right)+2 \\frac{d}{d x}\\left(e^{\\lambda x}\\right)+5 e^{\\lambda x}=0"

Substitute:


"\\frac{d^{2}}{d x^{2}}\\left(e^{\\lambda x}\\right)=\\lambda^{2} e^{\\lambda x} \\text{ and } \\frac{d}{d x}\\left(e^{\\lambda x}\\right)=\\lambda e^{\\lambda x}"


"\\lambda^{2} e^{\\lambda x}+2 \\lambda e^{\\lambda x}+5 e^{\\lambda x}=0"

Factor out "e^{\\lambda x} :"


"\\left(\\lambda^{2}+2 \\lambda+5\\right) e^{\\lambda x}=0"

Since "e^{\\lambda x} \\neq 0" for any finite "\\lambda" , the zeros must come from the polynomial:


"\\lambda^{2}+2 \\lambda+5=0"

Solve for "\\lambda" :


"\\lambda=-1+2 i \\text{ or } \\lambda=-1-2 i"


"\\text{The roots } \\lambda=-1 \\pm 2 i \\text{ give } y_{1}(x)=c_{1} e^{(-1+2 i) x}, y_{2}(x)=c_{2} e^{(-1-2 i) x} \\text{ as solutions, }\\\\\n\\text{ where } c_{1} \\text{ and } c_{2} \\text{ are arbitrary constants. }\n\\text{ }\\\\\n\\text{The general solution is the sum of the above solutions: }\\\\\ny(x)=y_{1}(x)+y_{2}(x)=c_{1} e^{(-1+2 i) x}+c_{2} e^{(-1-2 i) x}\n\\text{Apply Euler's identity } e^{\\alpha+i \\beta}=e^{\\alpha} \\cos (\\beta)+i e^{\\alpha} \\sin (\\beta):\\\\\ny(x)=c_{1}\\left(e^{-x} \\cos (2 x)+i e^{-x} \\sin (2 x)\\right)+c_{2}\\left(e^{-x} \\cos (2 x)-i e^{-x} \\sin (2 x)\\right)\\\\\n\\text{ }\\\\\n\\text{Regroup terms:}\\\\\ny(x)=\\left(c_{1}+c_{2}\\right) e^{-x} \\cos (2 x)+i\\left(c_{1}-c_{2}\\right) e^{-x} \\sin (2 x)\\\\\n\\text{Redefine } c_{1}+c_{2} \\text{ as } c_{1} \\text{ and } i\\left(c_{1}-c_{2}\\right) \\text{ as } c_{2}, \\text{ since these are arbitrary constants: }\\\\\ny(x)=c_{1} e^{-x} \\cos (2 x)+c_{2} e^{-x} \\sin (2 x)\\\\\n\\text{}\\\\\n\\text{Determine the particular solution to } \\frac{d^{2} y(0)}{d x^{2}}+2 \\frac{d y(x)}{d x}+5 y(x)=4 e^{-x}+17 \\sin (2 x)\\\\\n\\text{by the method of undetermined coefficients: }"


The particular solution will be the sum of the particular solutions to


"\\frac{d^{2} y(x)}{d x^{2}}+2 \\frac{d y(x)}{d x}+5 y(x)=4 e^{-x} \\text{ and } \\frac{d^{2} y(x)}{d x^{2}}+2 \\frac{d y(x)}{d x}+5 y(x)=17 \\sin (2 x)."

The particular solution to


"\\frac{d^{2} y(x)}{d x^{2}}+2 \\frac{d y(x)}{d x}+5 y(x)=4 e^{-x}"

is of the form:

"y_{p_{1}}(x)=a_{1} e^{-x}"

The particular solution to:


"\\frac{d^{2} y(x)}{d x^{2}}+2 \\frac{d y(x)}{d x}+5 y(x)=17 \\sin (2 x)"

is of the form:


"y_{p_{2}}(x)=a_{2} \\cos (2 x)+a_{3} \\sin (2 x)"

"\\text{Sum } y_{p_{1}}(x) \\text{ and } y_{p_{2}}(x) \\text{ to obtain } y_{p}(x): \\\\y_{p}(x)=y_{p_{1}}(x)+y_{p_{2}}(x)=a_{1} e^{-x}+a_{2} \\cos (2 x)+a_{3} \\sin (2 x)\\\\\n\\text{}\\\\\n\\text{Solve for the unknown constants } a_{1}, a_{2}, \\text{ and } a_{3} :\\\\\n\\text{Compute } \\frac{d y_{p}(x)}{d x} :\\\\\n\\begin{aligned} \\frac{d y_{p}(x)}{d x} &=\\frac{d}{d x}\\left(a_{1} e^{-x}+a_{2} \\cos (2 x)+a_{3} \\sin (2 x)\\right) \\\\ &=-a_{1} e^{-x}-2 a_{2} \\sin (2 x)+2 a_{3} \\cos (2 x) \\end{aligned}"


"\\begin{aligned} \\text { Compute } & \\frac{d^{2} y_{p}(x)}{d x^{2}}: \\\\ \\frac{d^{2} y_{p}(x)}{d x^{2}} &=\\frac{d^{2}}{d x^{2}}\\left(a_{1} e^{-x}+a_{2} \\cos (2 x)+a_{3} \\sin (2 x)\\right) \\\\ &=a_{1} e^{-x}-4 a_{2} \\cos (2 x)-4 a_{3} \\sin (2 x) \\end{aligned}"


"\\text{Substitute the particular solution } y_{p}(x) \\text{ into the differential equation: }\\\\\n\\frac{d^{2} y_{p}(x)}{d x^{2}}+2 \\frac{d y_{p}(x)}{d x}+5 y_{p}(x)=4 e^{-x}+17 \\sin (2 x)\\\\\na_{1} e^{-x}-4 a_{2} \\cos (2 x)-4 a_{3} \\sin (2 x)+2\\left(-a_{1} e^{-x}-2 a_{2} \\sin (2 x)+2 a_{3} \\cos (2 x)\\right)+\n5\\left(a_{1} e^{-x}+a_{2} \\cos (2 x)+a_{3} \\sin (2 x)\\right)=4 e^{-x}+17 \\sin (2 x)\\\\\n\\text{}\\\\\n\\text{Simplify:}\\\\\n4 a_{1} e^{-x}+\\left(a_{2}+4 a_{3}\\right) \\cos (2 x)+\\left(-4 a_{2}+a_{3}\\right) \\sin (2 x)=4 e^{-x}+17 \\sin (2 x)\\\\\n\\text{}\\\\\n\\text{Equate the coefficients of } e^{-x} \\text{ on both sides of the equation: }\\\\\n4 a_{1}=4\\\\\n\\text{}\\\\\n\\text{Equate the coefficients of } \\cos (2 x) \\text{ on both sides of the equation:}\\\\\na_{2}+4 a_{3}=0\\\\\n\\text{}\\\\\n\\text{Equate the coefficients of } \\sin (2 x) \\text{ on both sides of the equation:}\\\\\n-4 a_{2}+a_{3}=17"


Solving the system, we get:


"a_{1}=1\\\\\na_{2}=-4\\\\\na_{3}=1\\\\"

"\\text{}\\\\\n\\text{Substitute } a_{1}, a_{2}, \\text{ and } a_{3} \\text{ into } y_{p}(x)=e^{-x} a_{1}+\\cos (2 x) a_{2}+\\sin (2 x) a_{3}\\\\"


"y_{p}(x)=e^{-x}-4 \\cos (2 x)+\\sin (2 x)"

The general solution is:

"\\begin{aligned}\n&y(x)=y_{c}(x)+y_{p}(x)= \\\\\n&e^{-x}-4 \\cos (2 x)+\\sin (2 x)+c_{1} e^{-x} \\cos (2 x)+c_{2} e^{-x} \\sin (2 x)\n\\end{aligned}"


which is the required answer.


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog